Fertilizer Diversification as a Pathway to Agricultural Employment Growth in Central Java - Sucihatiningsih Dian Wisika Prajanti; Christina Litaay; Talitha Widiatningrum; Dhea Rizky Amelia; Tania Wicaksana (Universitas Negeri Semarang, 2025)
The production and application process of organic fertilizers generally requires additional labor compared to chemical fertilizers which are more instantaneous. Diversification of fertilizer use, especially the shift of some farmers to organic fertilizers, is not only driven by ecological considerations, but also by opportunities to increase economic added value that is labor intensive. This study aims to test and measure the extent to which diversification of organic and inorganic fertilizers has an impact on agricultural employment in Central Java. The analytical tools used are Labor Multiplier, Employment Opportunity Elasticity, and Employment Opportunity Growth Rate Calculation. The results of the analysis show that diversification of agricultural inputs in Central Java, especially through increased use of organic fertilizers, has a significant impact on job creation and sustainability of the agricultural sector. Although the allocation of organic fertilizer in the subsidy scheme is still low (around 4%), the trend of increasing adoption by farmers, the surge in certified land area, and the increase in the labor multiplier from 1.08 to 1.10 indicate that this environmentally friendly input has great potential as a labor-intensive lever of the village economy.